Assessment of Some Heavy Metals in Selected Cosmetics Commonly Sold in Katsina Markets and Their Human Health Risk - Surajo I.T.; Haruna A.; Kusharki H.M.; Ruma M.M.; Salisu A. (International Journal for Research in Applied Sciences and Biotechnology, 2021)
Cosmetic product protection is a serious concern because of the presence of heavy metals. Accumulation of these metals affect human body over a time. The study was aimed at assessing the levels of some toxic metals in different cosmetic products sold at different shops and markets in Katsina metropolis. The cosmetic items included nine face powder and nine lipsticks. The cosmetics were digested and analyzed for heavy metals (Ni, Cd, Cr and Pb) using Atomic Absorption Spectrophotometer. Risk of this metals to the consumer was determine using systematic exposure dosage (SED), margin of safety (MoS), hazard quotient (HQ), hazard index (HI) and cancer risk (CR). The range of the concentration in face powder was 0.007-0.624±0.003-1.508 mg/kg. The concentration ranges in lipsticks was 0.012-0.036 ± 0.009-0.036 mg/kg. Lead has the highest concentration in face powder and chromium has the highest concentration range in lipstick, while cadmiun has the least concentration in both face powders and lipsticks. The concentration of all the heavy metals are below permissible limit. The Margin of Safety (MoS) values calculated for different metals were higher than the established safe standard by WHO except for Cr in face powders. The obtained SED values are much lower than PTDI. HQ values were within permissible limit indicating low risk of detrimental effect. HI value is greater than one in face powder and less than one in lipsticks. The carcinogenic risk (CR) estimated are within permissible limit except for Cd.